2021
DOI: 10.1002/ejic.202100472
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolyl‐Appended Zinc Porphodimethenes: Branched Oligopyrrole Products From the Templated One‐Pot Isoporphyrin Synthesis

Abstract: The one-pot synthesis of zinc isoporphyrins from pyrrole, an aryl aldehyde and zinc acetate was investigated with regard to the formation of by-products. The optical spectra of the product mixtures differ strongly from each other depending on the aldehyde used and the water content in the solvent mixture of the condensation step. The compounds belonging to the two most prominent bands at approx. 500 nm and at approx. 640 nm could be isolated and structurally characterised. These are the homoleptic complexes (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…We also showed that the α-position of the appended pyrrole can be easily functionalized with functional groups such as −CHO 3 , and the functionalized meso -aryl 3-pyrrolyl BODIPYs have been used to synthesize several interesting fluorescent 3-pyrrolyl BODIPY-based conjugates . In due course of time, we and others have also developed a Lewis acid-catalyzed route to demask the BF 2 unit from BODIPYs, 3-pyrrolyl BODIPYs, and other BF 2 -complexes under very simple reaction conditions. Thus, tripyrrolic meso -aryl-pyrrolyl dipyrrins 4 are now easily available as ligands to explore their potential to form coordination complexes. , A perusal of the literature revealed that the dipyrrins and their derivatives have been used extensively as ligands for coordination chemistry, but the reports on tripyrrolic ligands and higher analogues or their derivatives are very few. In this paper, we used 3-pyrrolyl BODIPY 2 and α-formyl 3-pyrrolyl BODIPY 3 as key precursors to prepare one example of Ru­(II) complex 5 and three examples of BODIPY-Ru­(II) complexes 6 – 8 (Figure ) and explored their structure and spectral and redox properties using various experimental and theoretical methods. We have chosen 3-pyrrolyl BODIPY-based ligands which have the appended pyrrole “N” and either “O” of functionalized group as in 3 or “N” of substituent present at the α-position of appended pyrrole as in 9–10 to coordinate with Ru­(II) ion to form BODIPY-Ru­(II) complexes 6–8 .…”
Section: Introductionmentioning
confidence: 96%
“…We also showed that the α-position of the appended pyrrole can be easily functionalized with functional groups such as −CHO 3 , and the functionalized meso -aryl 3-pyrrolyl BODIPYs have been used to synthesize several interesting fluorescent 3-pyrrolyl BODIPY-based conjugates . In due course of time, we and others have also developed a Lewis acid-catalyzed route to demask the BF 2 unit from BODIPYs, 3-pyrrolyl BODIPYs, and other BF 2 -complexes under very simple reaction conditions. Thus, tripyrrolic meso -aryl-pyrrolyl dipyrrins 4 are now easily available as ligands to explore their potential to form coordination complexes. , A perusal of the literature revealed that the dipyrrins and their derivatives have been used extensively as ligands for coordination chemistry, but the reports on tripyrrolic ligands and higher analogues or their derivatives are very few. In this paper, we used 3-pyrrolyl BODIPY 2 and α-formyl 3-pyrrolyl BODIPY 3 as key precursors to prepare one example of Ru­(II) complex 5 and three examples of BODIPY-Ru­(II) complexes 6 – 8 (Figure ) and explored their structure and spectral and redox properties using various experimental and theoretical methods. We have chosen 3-pyrrolyl BODIPY-based ligands which have the appended pyrrole “N” and either “O” of functionalized group as in 3 or “N” of substituent present at the α-position of appended pyrrole as in 9–10 to coordinate with Ru­(II) ion to form BODIPY-Ru­(II) complexes 6–8 .…”
Section: Introductionmentioning
confidence: 96%